Strategi Pembelajaran Nilai Anti-Riba Melalui PAI Di Era Konsumerisme Digital - Supriatin, Iit; Ismail, Dudi; Mubarok, Mickail; Suciyati, Yati; Tresnajaya, Tresnajaya (PT. Student Rihlah Indonesia, 2025)
The phenomenon of digital consumerism among Muslim students has fostered a permissive mindset toward modern forms of riba (usury), such as online loans, digital installments, and concealed interest-based transactions. This study aims to analyze effective and relevant strategies for teaching anti-riba values in the digital era. A descriptive qualitative method was employed, based on a literature review of curriculum documents, textbooks, scholarly articles, and previous research. The findings indicate that although teachers are increasingly aware of the importance of Islamic commercial ethics (muamalah), classroom implementation remains theoretical and lacks contextual relevance. Identified teaching strategies include the integration of digital riba case studies, simulations of sharia-compliant transactions, and thematic approaches based on Qur’anic and Hadith evidences. The novelty of this study lies in the development of a responsive pedagogical model for anti-riba education tailored to students’ digital consumption realities. These findings have policy implications for strengthening the PAI curriculum with practical and applicable Islamic economic content, as well as the need for teacher training to implement contextual, muamalah-based learning in the digital age.